#failbetter. Issue 1 (April 2021) - Heron, Jonathan
Abstract : Recalling Beckett's treatment of failure ( Three Dialogues, 1949; Worstward Ho, 1983), this article considers 'fidelity to failure' as a performative and political issue. In dealing with both the aesthetics and ethics of Beckett's failure, the article is informed by recent publications and events within the field (Kenny ; Morin ; Maprayil; 2020 ). These interventions build upon a body of literature on Beckett (McMullan, 1994 ; Calder, 2001 ; Anderton, 2016 ; Thomas, 2018) and culture (Bersani and Dutoit, 1993 ; Ridout, 2006 ; Bailes, 2011 ; Halberstam, 2011 ). The article examines the phenomenon of failure within Beckettian production and wider ethical implications surrounding the (mis)appropriations of 'failing better'. Having established the uses – and misuses – of this phrase, the article proceeds in three interlinked parts: a) aesthetic failure in Beckett's creative practice through to his legacy in experimental theatre and popular culture; b) performance more broadly, including intersections with disability culture and queer studies; and c) performative interventions in public discourse, from Brexit in Europe to the 2016 US Presidential Election as well as social movements such as Black Lives Matter.